2022
DOI: 10.1002/adma.202203558
|View full text |Cite
|
Sign up to set email alerts
|

Spintronic Physical Unclonable Functions Based on Field‐Free Spin–Orbit‐Torque Switching

Abstract: Physical unclonable function (PUFs) utilize inherent random physical variations of solid‐state devices and are a core ingredient of hardware security primitives. PUFs promise more robust information security than that provided by the conventional software‐based approaches. While silicon‐ and memristor‐based PUFs are advancing, their reliability and scalability require further improvements. These are currently limited by output fluctuations and associated additional peripherals. Here, highly reliable spintronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…PUF is a security device that takes advantage of inherent randomness-which occurs during the manufacturing process unpredictably-as a security primitive. [12][13][14][15][16][17][18][19][20][21][22] This device is considered superior when the degree of randomness in the information it stores is high, thus lowering its susceptibility to brute-force attacks. However, utilizing magnetic spin glass patterns as a PUF device is impractical because they can be observed under strong magnetic fields and extremely low temperatures, significantly increasing the authentication complexity.…”
Section: Introductionmentioning
confidence: 99%
“…PUF is a security device that takes advantage of inherent randomness-which occurs during the manufacturing process unpredictably-as a security primitive. [12][13][14][15][16][17][18][19][20][21][22] This device is considered superior when the degree of randomness in the information it stores is high, thus lowering its susceptibility to brute-force attacks. However, utilizing magnetic spin glass patterns as a PUF device is impractical because they can be observed under strong magnetic fields and extremely low temperatures, significantly increasing the authentication complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they suffered from the well-known read-disturb challenge of resistive memories, [42][43][44][45] which reduces the CRP reliability if frequently used. Recently, PUF designs based on spin orbit torque (SOT) have also been proposed, [46][47][48][49][50][51] where the entropy comes from the variations of exchange bias in field-free perpendicular SOT devices, or from the stochasticity of the SOT-induced switching dynamics. A PUF based on voltage-controlled magnetic anisotropy (VCMA) has also been recently proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] For example, Zhang et al [13] demonstrated two types of rPUFs in Ta/CoFeB/MgO heterojunction based on process-induced SOT switching current variations and SOT-induced nonlinear domain wall dynamics, where an in-plane assistant magnetic field was needed to achieve deterministic SOT switching. Lee et al [14] further demonstrated highly reliable spintronic PUFs based on field-free SOT switching in IrMn/CoFeB/Ta/ CoFeB heterojunction, where randomizing the magnetization direction of the exchange-biased bottom CoFeB layer through field annealing was crucial. The presence of an external magnetic field could make the device design more complex.…”
mentioning
confidence: 99%
“…Accordingly, many rPUFs have been explored through various approaches, [6,7] including optical rPUFs, [8] phase change memory rPUFs, [9] resistive random access memory rPUFs, [10,11] spin-transfer torque magnetic random access memory rPUFs, [12] and spinorbit torque (SOT) based rPUFs. [13,14] Especially, SOT-based rPUFs have attracted increasing attention because SOT-induced magnetization switching has the advantages of low power consumption, fast switching speed, and high endurance. [15,16] For example, Zhang et al [13] demonstrated two types of rPUFs in Ta/CoFeB/MgO heterojunction based on process-induced SOT switching current variations and SOT-induced nonlinear domain wall dynamics, where an in-plane assistant magnetic field was needed to achieve deterministic SOT switching.…”
mentioning
confidence: 99%